EKSTRAKSI DAN PREPARASI GLUKOMANAN UMBI PORANG (Amorphophallus muelleri Blume) SEBAGAI EDIBLE FILM - Juntia Kirana Pratiwi; Subur P. Pasaribu; Chairul Saleh; Aman Sentosa Panggabean (PROSIDING SEMINAR KIMIA, 2023)
Glucomannan extracted from porang tubers (Amorphophallus muelleri Blume) can be used as a raw material for made edible films. In this research, extraction of glucomannan with graded ethanol method resulted in a yield of 10% and the composition of the edible film forming solution used was 6% glucomannan porang tubers and 25% (w/w) glycerol. The resulted edible film was clear and transparent with the characteristics tested are water content, thickness and water vapor transmission respectvely 20.16%, 0.15 m2 and 22.89 g/m2/hour. Based on the results of SEM analysis showed that the surface of the edible film of glucomannan porang tubers, the morphology of the surface was somewhat smooth but still less homogeneous. So, efforts are still needed to improve the characteristics so that to acording the required standards Keywords: Preparation, edible film, glucomannan, porang tubers